PENGARUH LATIHAN TAICHI TERHADAP STRES DAN KEPUASAN KERJA (STUDI PADA PERAWAT I.C.U. RUMAH SAKIT X) - Insan Firdaus (Faculty of Psychology, Atma Jaya Catholic University of Indonesia, 2015)
This study aimed to determine the correlation between work stress and job satisfaction, effect of taichi on work stress. Participants numbered 23 nurses. Data processing techniques used were Pearson Correlation Test and Analysis Variance Test. Results of this study showed no correlation between work stress (M = 1.826, SD = 0.467) and job satisfaction (M = 2.63, SD = 0.534), r(21) = 0.164, p = 0.454 > 0.05. Based on Anaylisis Variance test showed that control group 1.65 (SD = 0.647) and experiment group 1.33 (SD = 0.577). this research found that taichi has negative and significant influence on work stress. F(1,21) = 1.553 , p = 0.226 > 0.05.